O desenvolvimento da carreira em adultos pouco escolarizados - Gonçalves, Susana Raquel Teixeira (2011)
O objectivo desta tese é analisar as trajectórias de carreira de adultos pouco escolarizados em processo de RVCC, prosseguindo-se na linha de investigação sobre a educação e o desenvolvimento da carreira na vida adulta. Conceptualmente, o estudo empírico baseia-se nas teorias do desenvolvimento humano do adulto, com a teoria das transições de vida de Nancy Schlossberg e as abordagens desenvolvimentista de carreira, em especial, na teoria de Donald Super e Hall. Foi utilizado o método da análise qualitativa, com uma análise de conteúdo às respostas dadas a uma medida auto-biográfica – Actividades “O meu trajecto de vida” e “A minha auto-biografia”, de um grupo de adultos em processo RVCC (N=20, 55% homens; M=38 anos; 85% com o 2º ciclo e 15% com o 1º ciclo) na zona Norte do País no Centro de RVCC da Associação Empresarial de Portugal. A trajectória de carreira dos adultos estudados caracteriza-se por um abandono precoce dos estudos e sucessivas transições de emprego. Foram identificadas diferentes categorias de motivos de satisfação (as pessoas, o processo de aprendizagem académica, a transição de vida e os ambientes físico/relacionais) e de insatisfação (pessoas, processo de aprendizagem académica, ensino/aprendizagem e transição) com a escolaridade, bem como de satisfação (valores profissionais, competências e aptidões, interesses, condições físicas materiais e sociais e pessoas) e de insatisfação (acontecimentos críticos, valores profissionais, condições físicas relacionais e variedade/mudanças constantes) com a vida profissional. Foram ainda identificados como motivos principais de abandono precoce dos estudos as seguintes categorias: transição de vida, motivos familiares, insucesso escolar e comportamento. Com a análise das auto-biografias dos adultos, muitas outras categorias surgem, reflectindo os principais temas de vida dos adultos. Deste estudo, retiram-se implicações para a intervenção psicoeducacional e de carreira junto de adultos pouco escolarizados. ABSTRACT: The aim of this study is to analyse the career paths of adults who left school at an early age and are now attending a process of skills recognition, validation and accreditation of skills (RVAS). It follows the investigation line or education and career development throughout the adult life. From the conceptual point of view, the empiric study is supported by the theories related to the adult’s human development as well as theories of Nancy Schlossberg’s theory of life transitions and on career development approaches, namely the theories from Donald Super and Hall. This work used the qualitative analysis method, based on the content analysis of answers given autobiographically – Activity “My life path” and “My autobiography”, from a group of adults attending a RVAS process (N=20, 55% men and 45 % women; M=38 years old; 85% with the elementary school completed and 15% with the primary school completed) in the country’s Northern region, specifically in the RVAS Centre of the Portuguese Business Association. The career path from the studied adults is characterised by an early school abandon and successive job changes. There have been identified different categories for reasons of satisfaction about school (the people, the academic learning process, life transitions and physical/relational environments) and for reasons of dissatisfaction about school (People, the academic learning process, education/learning and transition). In addition, there have also been identified categories of satisfaction (professional values, skills and abilities, interests, material and social physical conditions and people) and of dissatisfaction (critical events, professional values, physical relational conditions and frequent changes) as far as the professional life is concerned. At last, there have also been identified as main reasons for school early abandon the following categories: life transition, family issues, failure at school and behaviour). According to the adults autobiographies analyses, many others categories appear reflecting the many themes of the adults life. With this study it is possible to help on building psychological and educational interventions next to adults who left school at an early age. According